Integrasi Artificial Intelligence dalam Pendidikan Agama Islam - Latifah (Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the integration of Artificial Intelligence (AI) in Islamic Religious Education (PAI), encompassing its opportunities, challenges, and implications for the learning process and students’ character development. The method employed is a qualitative study with a descriptive-analytical approach through literature review and conceptual analysis of AI implementation in education. The findings indicate that AI can enhance the effectiveness of PAI learning through personalized content delivery, automated assessment, and the provision of adaptive learning resources. However, the integration of AI also presents several challenges, particularly related to ethical concerns, technological dependency, and the potential reduction of spiritual values if not managed wisely. Therefore, an integrative model that combines AI technology with Islamic values is necessary to ensure that PAI learning remains oriented toward moral and character formation. This study recommends the development of a technology-based PAI curriculum that continues to prioritize moral and spiritual dimensions as the fundamental foundation of Islamic education in the digital era.